The nurse as an agent of transformation in infection prevention in the Neonatal Intensive Care Unit (NICU) (Research, Society and Development, 2025)
Introduction: Hospital-acquired infections in Neonatal Intensive Care Units (NICUs) constitute a serious public health problem, with a significant impact on neonatal morbidity and mortality. Nursing, as the primary provider of direct care for newborns, plays a fundamental role in the prevention and control of these infections. Objectives: This study aims to analyze nursing's role in infection prevention and control in NICUs, identifying best practices. Methods: Data analysis was performed using a descriptive and thematic framework. Ten studies that met the inclusion criteria and answered the guiding question were selected. An integrative literature review was conducted in the MEDLINE, LILACS, BDENF, and PubMed databases. Articles were selected between 2019 and 2025, in Portuguese and English. Results: The results highlight the need for specialized care in the neonatal intensive care unit, strengthened training for nursing professionals, and greater focus on the control and prevention of hospital-acquired infections, as well as daily hygiene and humanized care. Conclusion: The study demonstrated that nursing care in infection prevention and neonatal and family well-being is fundamental. However, nurses face several challenges that impact this work, such as resource scarcity, professional overload, and the need for greater recognition of this service. Therefore, the need for greater recognition of nursing in this setting still represents barriers to the implementation of this care model.